1974
DOI: 10.1002/ajpa.1330410202
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase isoenzymes in nine troops of Kenya baboons, Papio cynocephalus (Linnaeus 1766)

Abstract: The distributions of alleles at the carbonic anhydrase I (CAI = CAB) and carbonic anhydrase I1 (CA I1 = CA C) loci in nine troops of Papio cynocephalus were determined. Two alleles were found at the C A I locus, and three at the CA I1 locus; the frequencies were: CA I" = 0.856; CA I b = 0.144; CA IIa = 0.784; CA IIb = 0.209; C A 11" = 0.007. Results of tests for HardyWeinberg equilibrium, homogeneity tests, and calculations of migration rates were used in support of the interpretation that migration and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The author's estimate of average migration rate (~) among three troops ofhamadryas baboons was 0.12 and this would seem to be comparable to those obtained among the anubis troops studied by OLIVIER, BUETTNER-JANUSCH and BUETTNER-JANUSCH (1974), the distribution area of the troops being approximately equal and the effective population sizes being in a same range. They estimated ~ in the range from 0.094 to 0.214 corresponding to N (effective population size) varying from 85 to 30.…”
Section: Migration Rates Among Neighbouring Populationssupporting
confidence: 66%
See 1 more Smart Citation
“…The author's estimate of average migration rate (~) among three troops ofhamadryas baboons was 0.12 and this would seem to be comparable to those obtained among the anubis troops studied by OLIVIER, BUETTNER-JANUSCH and BUETTNER-JANUSCH (1974), the distribution area of the troops being approximately equal and the effective population sizes being in a same range. They estimated ~ in the range from 0.094 to 0.214 corresponding to N (effective population size) varying from 85 to 30.…”
Section: Migration Rates Among Neighbouring Populationssupporting
confidence: 66%
“…(Table 4). OLIVIER, BUETTNER-JANuSCH and BUETTNER-JANUSCH (1974) found two polymorphisms only at the CA loci of olive baboon, Papio anubis, living in the Laipikia district of northern Kenya, It is a somewhat surprising that despite the anubis baboons, Papio anubis, have the widest distribution of the genus Papio, they have maintained a relatively smaller variability compared with the more peripheral species. OLIVIER, BUETTNER-JANuSCH and BUETTNER-JANUSCH (1974) found two polymorphisms only at the CA loci of olive baboon, Papio anubis, living in the Laipikia district of northern Kenya, It is a somewhat surprising that despite the anubis baboons, Papio anubis, have the widest distribution of the genus Papio, they have maintained a relatively smaller variability compared with the more peripheral species.…”
Section: Migration Rates Among Neighbouring Populationsmentioning
confidence: 99%
“…As a few species of baboons, that is, hamadryas (Papio hamadryas) and gelada (Theropithecus gelada) baboons, possess an unusual hierarchical structure, they cannot be directly compared with the above species [for population genetical studies of baboon, see SrIoT"A~zz, NOZAWA & TANABE (1977) and SHOTAKli (~ NOZAWA (in press)]. Studies on Kenyan olive baboons (Papio cynocephalus) suggested that male migration and species-specific behavior relating sex and age had caused the observed local genetic differentiation among troops (OBER, OLIVIER & BUETTNER-JANUSCH, 1978;OLIVIER, BUETTNER-JANUSCH & BUETTNER-JANUSCH, 1974).…”
Section: Introductionmentioning
confidence: 96%
“…The CA2 system has been widely investigated among Old World monkeys and has been shown to be polymorphic in several species of the genus Macaca (TASHIAN et al, 1971;VANDEBERG et al, 1982) and in Papio cynocephalus (OLIvIER et al, 1974). Monomorphism has been observed in Papio anubis and Papio hamadryas (SHoTAKE, 1981).…”
Section: Resultsmentioning
confidence: 99%